Using the software «DAWN AC» for control of dosing warfarin in the special anticoagulation clinics - O. S. Napalkova; V. L. Emanuel; M. A. Karpenko; S. V. Lapin (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2015)
Warfarin remains the drug of choice for the prevention of ischemic stroke, thus optimization of methods of control of dosing this preparation becomes more topical. The aim of our study was to test computer software for monitoring anticoagulant therapy with warfarin in patients with atrial fibrillation based on the day anticoagulant hospital. A total of 6 people with atrial fibrillation undergoing treatment with warfarin in specialized outpatient clinics were monitored with the software for 3 to 6 months. At the same time, comparable 11 patients with atrial fibrillation were followed by experienced clinician. Both groups were matched by sex, age and clinical diagnosis. The comparison group consisted of 11 patients diagnosed with the same disease, of the same gender and age. We have found that in patients followed by anticoagulation software the time spent in the therapeutic INR range was twice the time in therapeutic range of patients in which the dosing and follow-up was done by experienced doctor (p